POLA MAKAN DAN POLA AKTIFITAS PADA ANAK OBESITAS DI SD ISLAM AL-HIKMAH SELOKERTO KECAMATAN SEMPOR KABUPATEN KEBUMEN - Ning Iswati; Neza Desyarti; Nurlaila Nurlaila (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2018)
Obesity has become a worldwide health problem. Obesity is the impact of energy imbalances over a period of time. Many factors cause excessive obesity, but these can be simplified into eat more and move less. The purpose to know dietary habit and activity pattern towards obesity of elementary school children in Al-Hikmah Islamic Elementary School at Selokerto, Sempor, Kebumen. This research is an analytic research with total sampling technique as many as 34 respondents. Data collection was done by filling out the questionnaires with univariat analysis.Based on the research conducted, finding out 61,8% of children have good dietary habit and 41,2% of them have less activity. Children with obesity have good dietary habit and children have less activity. Since there is it is possibly related by other factors, such as genetic, socioeconomic, environment, hormonal, psikologis and gender. There should be next reseach on the other factors, such as genetics, socioeconomic, environmental, hormonal, psychological and gender. Key word : activity patterns, dietary habit, obesity